Explaining Financial Satisfaction in SMEs: The Role of Financial Knowledge, Behavior, and Risk Attitude - Putra, Arbi Adi; Gani, Nuraeni; wahyudiyud (Study of Scientific and Behavioral Management, 2023)
ABSTRACT Information technology can be used to make it easier to carry out activities contained within the company. Information technology can also be used to improve individual performance as a member of a business organization which in aggregate is required to improve the performance of an organization. This research is a quantitative research, with a sample research method of 50 people from PT. ABC Energy, Jeneponto Regency. The sample method used in this study is a saturated sample, where all populations are used as samples in this study. From the results of the research that has been done, it can be concluded that: it is concluded that Mastery of Information Technology is able to influence the relationship of Knowledge of Information Technology to Employee Performance at PT. ABC Energy, Jeneponto Regency. Keywords: Information Technology Knowledge, Information Technology Mastery, and Employee Performance